Stacking engineering induced Z-scheme MoSSe/WSSe heterostructure for photocatalytic water splitting - Ren, Longjun; Liu, Zongfa; Ma, Zhen; Ren, Kai; Cui, Zhen; Mu, Weihua (Frontiers in Chemistry, 2024)
Stacking engineering is a popular method to tune the performance of two-dimensional materials for advanced applications. In this work, Jansu MoSSe and WSSe monolayers are constructed as van der Waals (vdWs) heterostructure by different stacking configurations. Using first principle calculations, all the relaxed stacking configurations of the MoSSe/WSSe heterostructure present semiconductor properties, while the direct type-II band structure can be obtained. Importantly, Z-scheme charge transfer mode also can be addressed by band alignment, which shows the MoSSe/WSSe heterostructure is an efficient potential photocatalyst for water splitting. Besides, the built-in electric field of the MoSSe/WSSe vdWs heterostructure can be enhanced by S-Se interface due to further asymmetric structures, which also results considerable charge transfer comparing with the MoSSe/WSSe vdWs heterostructure built by S-S interface. Furthermore, the excellent optical performances of the MoSSe/WSSe heterostructure with different stacking configurations are obtained.Our results provide a theoretical guidance for the design and control of two-dimensional heterstructure as photocatalysts through structural stacking.